Validation of the Spanish version of the Wong Law Emotional Intelligence Scale (WLEIS-S) - Extremera-Pacheco, Natalio; Rey-Peña, Lourdes; Sánchez-Álvarez, Nicolás (Colegio Oficial de Psicología del Principado de Asturias, 2019)
Background: The Wong and Law Emotional Intelligence Scale (WLEIS) is a self-report emotional intelligence scale based on the theoretical framework of Mayer & Salovey (1997). The aim of this study was to examine the psychometric properties of the Spanish version of the Wong and Law Emotional Intelligence Scale (WLEIS; Wong & Law, 2002) in a large sample of 1,460 adults (815 women and 645 men) ranging from 17 to 64 years old (M = 33.27, SD = 11.60). Method: The scale was back-translated and participants completed a battery of questionnaires including the Spanish WLEIS (WLEIS-S), perceived stress scale, subjective happiness scale, life satisfaction scale, and suicide behavioural questionnaire. Results: The results provided evidence of adequate internal consistency and criterion validity consistent with the original version. Confi rmatory factor analysis showed a four-factor structure with good fi t. Finally, gender differences were found in the overall EI score and on the appraising the emotion of others dimension, with women scoring higher than men. Conclusions: Overall our results provide evidence that the WLEIS-S might be a promising tool for the assessment emotional intelligence in the Spanish context.
Keywords: Inteligencia emocional - Tests; Wong and Law Emotional Intelligence Scale; Spanish validation; measurement; factorial validity; criterion validity